Eros, Eucharist, and the Poetics of Desire. - GLOVER, ADAM (Logos: A Journal of Catholic Thought & Culture)
The article offers information on the works of poet Francisco Luis Bernárdez on eroticism. Topics discussed include poem "The City without Laura" mentions about the erotic character of sacramentality and the sacramental character of eros; poem "Aesthetics of the Cup of Water," mentions about the divine will, and poem "Poem of the Eucharistic Bread" mention about unassuming meditation on the Eucharist.